'Not Becoming Mother': A Phenomenological Exploration of the Therapeutic Relationship with Transgender Clients. (2nd January 2018) - Harmon, Kevin; Donohue, Gráinne
ABSTRACT: LGBTI clients present specific challenges for the mental health profession with key issues for transgender people identified as including isolation, fear, stigma, and family rejection, all of which contribute to the transgender community's high levels of depression, anxiety, substance misuse, self-harm, and suicide. This qualitative research paper explores the experiences of Irish psychotherapists working with transgender clients to explore specifically the nature of the therapeutic relationship. Using an interpretive phenomenological approach, it examines the subjective experience of three participant psychotherapists and endeavours to make sense of the phenomenology that emerged from semi-structured interviews. The phenomenological analysis of the data collected resulted in three salient themes emerging: (i) Therapeutic identification, (ii) Maternal countertransference, and (iii) Confusion. It is hoped that these findings which relate to the therapeutic relationship will be of utmost importance to others working within the mental health profession where recovery is dependent on the strength of this relationship.